LPS Mediates Bovine Endometrial Epithelial Cell Pyroptosis Directly Through Both NLRP3 Classical and Non-Classical Inflammasome Pathways - Ma, Xiaoyu; Li, Yajuan; Shen, Wenxiang; Oladejo, Ayodele Olaolu; Yang, Jie; Jiang, Wei; Imam, Bereket Habte; Wu, Xiaohu; Ding, Xuezhi; Yang, Ying; Wang, Shengyi; Yan, Zuoting (Frontiers in Immunology, 2021)
As a highly inflammatory form of programmed cell death, pyroptosis is triggered by pro-inflammatory signals and associated with inflammation. It is characterized by cell swelling and large bubbles emerging from the plasma membrane, which release cytokines during inflammation. Compared with other types of cell death, pyroptosis has a distinct morphology and mechanism and involves special inflammasome cascade pathways. However, the inflammasome mechanism through which endometrial epithelial cell pyroptosis occurs in LPS-mediated inflammation remains unclear. We confirmed that there was an increased mRNA and protein expression of the IL-6, TNF-α, IL-1β, IL-18 cytokines, the inflammasome molecules NLRP3, CASPASE-1, CASPASE-4, and GSDMD in LPS-induced primary bovine endometrial epithelial cells (BEECs) in an in vitro established inflammatory model using ELISA, real-time PCR (RT-PCR), vector construction and transfection, and Western blotting. Scanning electron microscopy and lactate dehydrogenase (LDH) activity assays revealed induced cell membrane rupture, which is the main characteristic of pyroptosis. In conclusion, the cytolytic substrate GSDMD’s cleavage by caspase-1 or caspase-4 through the NLRP3 classical and non-classical inflammasome pathways, GSDMD N-terminus bind to the plasma membrane to form pores and release IL -18, IL-1β cause cell death during LPS induced BEECs inflammation.